Playing YouTube: How the Nancy YouTuber doll and app position children as aspiring YouTube influencers. - Ruiz-Gomez, Alexandra; Leaver, Tama; Abidin, Crystal (2021)
This article analyzes Nancy YouTuber, a popular doll and companion app that is part of a growing trend of children's toys modeled on YouTube influencers. Nancy YouTuber's app is one of the first to provide a fictitious YouTube channel, introducing children to YouTube's affordances. We investigate how the doll and app socialize YouTuber practices, and to what extent the combination of both deepens the commodification of childhood. We use the walkthrough method to analyze the app, and a semiotic approach to study the doll, its accessories and surrounding materials to map the manufacturer's intended use through these discourses. Our research uncovers how children are encouraged to recreate product reviews and internalize commercial digital identity performances. We use Spain, where the doll originates, to contextualize these findings. The article considers how influencer-aspirant toys position children as promotional intermediaries and normalize children's YouTuber aspirations.